HUBUNGAN KEIKUTSERTAAN KELAS IBU HAMIL DAN DUKUNGAN SOSIAL KELUARGA DENGAN PERILAKU PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU - Rida Pertiwi; Suyatno Suyatno; Dharminto Dharminto (Jurnal Kesehatan Masyarakat (Undip), 2017)
A cause for infant mortality is low exclusive breastfeeding for the first 6 months of baby’s life. Many factors indicated as a coverage decreased indicator exclusive breastfeeding one of them is low participation and the excecution of antenatal class. Data from Health Office of Central Java Province showed that the coverage of exclusive breastfeeding is 58,4%. In Semarang city showed the number is 57,29% at infants aged 0-6 months. The purpose of this study was to analyze the relationship of participation of antenatal class and family social support with exclusive breastfeeding behavior in the community health center Kedungmundu. This research is descriptive analitic study with cross-sectional design. The population in this study were 504 mothers who had baby aged 6-12 months which involving 76 samples which selected using random sampling. Analysis of data using Chi-Square test (p=0,05). The result showed that the majority of the respondents aged 20-35 years (85,5%), more than half the education level of the respondents were in high school graduates (60,5%), more than half of respondents work are housewives (51,3%), majority of the respondents has high knowledge (61,8%), good attitude (64,5%) and good practice (57,9%) in exclusive breastfeeding. There was a relationship between participation of antenatal class with knowledge (p=0,037) and practice (p=0,017) in exclusice breastfeeding. There was no relationship between participation of antenatal class with attitude in exclusive breastfeeding (p=0,338). There was a relationship between family support with practice in exclusive breastfeeding (p=0,026). There was no relationship between family support with knowledge (p=0,887) and attitude (p=0,726) in exclusive breastfeeding. It was concluded that participation of antenatal class dan family support have relationship with exclusive breastfeeding practice.